How it will happen and what it will mean (New York, 1991)
Imagine looking at your computer screen and seeing reality--an image of your city, for instance, complete with moving traffic patterns, or a picture that sketches the state of an entire corporation at this second. These representations are called Mirror Worlds, and according to David Gelernter they will soon be available to everyone. Mirror Worlds are high-tech voodoo dolls: by interacting with the images, you interact with reality. Indeed, Mirror Worlds will revolutionize the use of computers, transforming them from (mere) handy tools to crystal balls which will allow us to see the world more vividly and see into it more deeply.
Keywords: Computer software,Software engineering